Analisa Bahasa Bentuk Pada Desain Karakter Film Animasi “Spirited Away” - Pratiwi, Wilsa (Jurnal Desain Komunikasi Visual Asia, 2024)
Creating character designs requires several stages in the process, and one of the knowledge that a designer must have is about shape language. The use of form language to make character designs easier for the audience to understand. Form language is a form of communication with certain meanings to create the desired character. Studio Ghibli is a popular animation studio known in various countries, one of the animated films made by Ghibli which has unique and iconic characters is "Spirited Away". The story, which is closely related to superstition, myth and legend, ultimately gives rise to very diverse and interesting types of characters to be discussed. The author wants to analyze the form of language that can be read from the characters in the film "Spirited Away", they are Chihiro, Haku, Kaonashi, Yubaba and Zeniba, Lin, Kamaji and Radish Spirit. The author wants to examine what basic types appear in the characters of this film, what use of shape language appears, and whether there is a match between the meaning of shape language and the traits or personality possessed by each character. It is hoped that the conclusions obtained will provide insight or additional knowledge in creating character designs through shape language theory.